OPTIMIZING ORTHODONTIC TREATMENT PROTOCOLS FOR DISTAL OCCLUSION (ANGLE CLASS II MALOCCLUSION): EVIDENCE SYNTHESIS, DECISION PATHWAYS, AND PROTOCOL OPTIMIZATION ACROSS THE LIFESPAN (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Distal occlusion (Angle Class II malocclusion) is a highly prevalent sagittal discrepancy that encompasses heterogeneous etiologies and phenotypes, including maxillary protrusion, mandibular retrognathia, dentoalveolar compensation, and functional disturbances. Optimizing treatment therefore requires structured diagnosis and deliberate selection among growth modification, orthodontic camouflage, skeletal anchorage strategies, and orthognathic surgery. This scholarly review synthesizes contemporary primary studies, systematic reviews, and clinical guidance to propose an evidence‑informed framework for optimizing Class II protocols across children, adolescents, and adults.